2007
DOI: 10.7124/bc.00076f
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of serine/threonine protein phosphatase 5 with the protein products of tumour suppressor gene Tsc2

Abstract: Tuberous sclerosis (TSC) is a tumour disease caused by mutations in Tsc1 or Tsc2 genes. Both protein products of Tsc1 and Tsc2 form an intracellular complex possessing GTPase-activating (GAP) activity towards a small GTP binding protein Rheb. The activity of TSC1/2 complex is regulated by multiple phosphorylations of TSC2 mediated by several kinases, such as PKB/Akt, AMP-activated kinase (AMPK), ERK, MK2 and RSK1. So far, very little is known about the molecular mechanisms of TSC2 dephosphorylation. In the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…However so far, very little is known about the molecular mechanisms of TSC2 dephosphorylation. In the yeast two-hybrid screening, we have identified a number of potential TSC2 binding partners including a protein phosphatase 5 (PP5) [51][52]. We provided the evidence that the interaction between TSC2 and PP5 also occurs in mammalian cells and found that this interaction is stronger in exponentially growing and serum stimulated cells when compared to serum starved cells.…”
mentioning
confidence: 99%
“…However so far, very little is known about the molecular mechanisms of TSC2 dephosphorylation. In the yeast two-hybrid screening, we have identified a number of potential TSC2 binding partners including a protein phosphatase 5 (PP5) [51][52]. We provided the evidence that the interaction between TSC2 and PP5 also occurs in mammalian cells and found that this interaction is stronger in exponentially growing and serum stimulated cells when compared to serum starved cells.…”
mentioning
confidence: 99%
“…Recently we have identified PP5 as a new binding partner for a TSC2, a component of tuberous sclerosis complex TSC1/2 [28][29][30]. TSC1/2 complex serves as a point of integration between growth-stimulatory and growth-suppressive signaling upstream of mTOR in PI3Ê/Akt/mTOR signaling pathway.…”
mentioning
confidence: 99%
“…Previously we have reported that serine/threonine protein phosphatase 5 (PP5) is a novel binding partner of TSC2 [13]. Furthermore, we demonstrated that PP5 interacts specifically with TSC2 not only in yeast two-hybrid system, but also in mammalian cells [14]. In order to establish functional link between TSC1/TSC2 and PP5 we studied the protein complex formation in starved cells and in response to serum stimulation.…”
mentioning
confidence: 99%
“…Materials and Methods. Culturing and transfection of TSC2 +/+ p53 -/mouse embryonic fibroblasts (MEFs) was described previously in [14]. The production of anti-TSC2 mAbs (D6) is described in [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation